Plasmon resonance in warm dense matter. - Thiele, R; Bornath, T; Fortmann, C; Höll, A; Redmer, R; Reinholz, H; Röpke, G; Wierling, A; Glenzer, S; Gregori, G (2008)
Collective Thomson scattering with extreme ultraviolet light or x rays is shown to allow for a robust measurement of the free electron density in dense plasmas. Collective excitations like plasmons appear as maxima in the scattering signal. Their frequency position can directly be related to the free electron density. The range of applicability of the standard Gross-Bohm dispersion relation and of an improved dispersion relation in comparison to calculations based on the dielectric function in random phase approximation is investigated. More important, this well-established treatment of Thomson scattering on free electrons is generalized in the Born-Mermin approximation by including collisions. We show that, in the transition region from collective to noncollective scattering, the consideration of collisions is important.